ABCG2 variant has opposing effects on onset ages of Parkinson's disease and gout. (19th January 2015) - Matsuo, Hirotaka; Tomiyama, Hiroyuki; Satake, Wataru; Chiba, Toshinori; Onoue, Hiroyuki; Kawamura, Yusuke; Nakayama, Akiyoshi; Shimizu, Seiko; Sakiyama, Masayuki; Funayama, Manabu; Nishioka, Kenya; Shimizu, Toru; et al.
Abstract: Uric acid (urate) has been suggested to play a protective role in Parkinson's disease onset through its antioxidant activity. Dysfunction of ABCG2, a high‐capacity urate exporter, is a major cause for early‐onset gout based on hyperuricemia. In this study, the effects of a dysfunctional ABCG2 variant (Q141K, rs2231142) were analyzed on the ages at onset of gout patients ( N = 507) and Parkinson's disease patients ( N = 1015). The Q141K variant hastened the gout onset ( P = 0.0027), but significantly associated with later Parkinson's disease onset ( P = 0.025). Our findings will be helpful for development of more effective prevention of Parkinson's disease.